Midwives' competence and confidence in Kenya: a sequential explanatory study design - Edna, T; Kaura, D; Mash Bob (BMC Health Services Research, 2026)
Background: The competence and confidence of midwives are pivotal in delivering essential care during pre-pregnancy, pregnancy, childbirth, and postpartum for women and their newborns. This study explored midwifery competency gaps in Kenya to recommend evidence-based policies, aiming to enhance maternal and neonatal health outcomes and inform future interventions. Methods: This study utilised a sequential explanatory study design which includes integrating quantitative and qualitative approaches of data collection, analysis, and synthesis. The quantitative phase involved a cross-sectional survey assessing midwives’ competence and confidence based on the International Confederation of Midwives (ICM) domains. 2019. The qualitative phase consisted of interviews with midwives and stakeholders to further explore and elucidate the quantitative findings. Sampling, interpretation, and reporting were integrated throughout the design. Data collection occurred in two distinct phases: an initial quantitative survey followed by qualitative interviews using a qualitative descriptive explanatory design with selected midwives and stakeholders. Qualitative data was coded and analyzed using Atlas ti 9 software. Thematic analysis, based on the Colaizzi framework, was conducted to capture emerging meanings while preserving the essence presented by the informants. Quantitative data were analyzed using SPSS, with descriptive statistics and statistical significance tested using Pearson’s Chi-square and Kruskal-Wallis tests. Both qualitative and quantitative data were analyzed separately and then connected to explain the results, ensuring triangulation and complementarity for comprehensive insights. Results: Direct-entry diploma midwives (KRM) and those working in tertiary hospitals reported higher competence and confidence (P = 0.019, p < 0.001, Kruskal-Wallis). KRMs were more confident in the ICM labour and birth domain (p = 0.017). Qualitative analysis revealed four themes: qualifications, enabling environment, work experience, and optimizing midwifery. Findings suggest that direct entry midwifery programs’ duration and education significantly impact midwives’ skill development. Mentorship and clinical supervision enhanced midwives’ confidence in labour and delivery domains. No statistical correlation was found between competence and work experience, but qualitative findings highlighted the importance of continuous professional development, clinical teaching, and supervision. An enabling working environment with appropriate resources, guidelines, and a multi-disciplinary team of obstetrics experts supported the high competence and confidence levels of midwives in tertiary care. Conclusion: This study identifies midwifery competency gaps in Kenya and recommends strengthening continuous professional development, clinical teaching, and supervision to improve maternal and newborn outcomes. It fills a knowledge gap by exploring midwives’ self-perceived competence and confidence levels in various domains of International Confederation of Midwives (ICM) competency through a sequential explanatory study design.
Keywords: Competence; Confidence; Education; Explanatory sequential design; Kenya; Knowledge; Skills and behaviour.